Constraints Experienced by Teachers in Utilization of Educational Technology: A Study in State Agricultural University - Shantanu Rakshit and Gyanendra Sharma, (Indian Journal of Extension Education, 2015)
The study was conducted in Govind Ballabh Pant University of Agriculture and Technology, Pantnagar. Acomprehensiveand detailed pre-tested questionnaire was used for collecting information. Fifty per cent of teachers from each collegewere selected randomly in sample. Total 120 completely answered questionnaires were received. The respondents wereasked to express the constraints in the utilization of educational technologies. The mean score for a particular constraintwas worked out by dividing the weighted score of the constraints by the total number of respondents. The ranking ofconstraints was done according to the mean score of each statement. Lack of technical support was perceived as mostimportant constraint. Other important constraints were lack of maintenance of existing facilities; lack of funds; lack ofsupporting hardware and software; and lack of periodic reviews of the digital learning materials. Majority of the importantconstraints are related with infrastructure and administration.